2012
DOI: 10.1073/pnas.1112570109
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene-mediated alterations in chromatin conformation

Abstract: Emerging evidence suggests that chromatin adopts a nonrandom 3D topology and that the organization of genes into structural hubs and domains affects their transcriptional status. How chromatin conformation changes in diseases such as cancer is poorly understood. Moreover, how oncogenic transcription factors, which bind to thousands of sites across the genome, influence gene regulation by globally altering the topology of chromatin requires further investigation. To address these questions, we performed unbiase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
125
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 40 publications
5
125
0
Order By: Relevance
“…This observed relationship between ERG expression and gene specific DNA methylation is not surprising given the role of ERG as a transcription factor that likely requires epigenetic cofactors in modifying and remodeling surrounding chromatin to exert its effects. Recent functional work in ERG-overexpressing cells has identified global changes in chromatin interactions that are likely dependent on chromatin remodeling and epigenetic changes (36). Furthermore, ERG expression has been shown to correlate with HDAC1 expression and also induces EZH2 expression (37,38), both of which may cooperate with DNA methylation to promote a silent chromatin state (30,39).…”
Section: Discussionmentioning
confidence: 99%
“…This observed relationship between ERG expression and gene specific DNA methylation is not surprising given the role of ERG as a transcription factor that likely requires epigenetic cofactors in modifying and remodeling surrounding chromatin to exert its effects. Recent functional work in ERG-overexpressing cells has identified global changes in chromatin interactions that are likely dependent on chromatin remodeling and epigenetic changes (36). Furthermore, ERG expression has been shown to correlate with HDAC1 expression and also induces EZH2 expression (37,38), both of which may cooperate with DNA methylation to promote a silent chromatin state (30,39).…”
Section: Discussionmentioning
confidence: 99%
“…However, increasing evidence suggests that in addition to local interactions, 3D contacts between distal regulatory elements play an important role in gene regulation (Gondor and Ohlsson 2009;Schoenfelder et al 2010). Such contacts have been implicated in diverse biological phenomena including development, cancer, and immune response (Jhunjhunwala et al 2008;Kenter et al 2012;Rickman et al 2012;Apostolou et al 2013;Liu and Cheung 2013;PhillipsCremins et al 2013). However, due to the limited ability to study three-dimensional (3D) chromatin structure with sufficient breadth and resolution, our knowledge regarding the characteristics and impact of chromatin structure remains limited.…”
mentioning
confidence: 99%
“…Rickman et al, for example, found that overexpression of an oncogenic transcription factor in normal cells leads to large-scale changes in chromatin organization [36]. We have seen that there is a dramatic change in long-range interactions in cancer cells compared with cells derived from normal tissues.…”
Section: Discussionmentioning
confidence: 75%